Policy and marketing changes to help curb childhood obesity: government ban vs. industry self‐regulation. (September 2016) - Dumitrescu, Claudia; Shaw Hughner, Renée; Shultz, Clifford J.
Abstract: Childhood obesity has become a public health crisis requiring action from government and food marketers. Building on attribution theory, this study advances understanding of how parents respond to information about policies intended to restrict sales promotion (i.e. toy premiums) paired with children's fast food meals, the consumption of which is often linked to obesity. This research uses experimental design to test the effects of two types of sales promotion restrictions on parents' attitudes and behavioural intentions: industry self‐regulated restrictions and restrictions arising from government‐mandated policies. The results show that a toy premiums ban may lead to higher satisfaction with, and behavioural intentions toward, less‐healthy food products. These responses are explained by parents' minimized tendency to blame the food marketers for less‐healthy meals. The contributions of this research have theoretical and practical implications for policy makers, food marketers and consumer researchers.